The Morphometric Analysis of the Mental Foramen in Adult Dry Human Mandibles: A Study on the South Indian Population - K. Udhaya; K.V. Saraladevi; J. Sridhar (Journal of Clinical and Diagnostic Research, 2013)
Aim: The mental foramen is a small foramen which is located in the antero-lateral aspect of the body of the mandible. It is situated midway between the upper and the lower border of the mandible and it transmits the mental nerve and the vessels. The knowledge on the anatomy of the mental foramen is very important in clinical dentistry and in surgical procedures which involve that area. Material and Methods: Our study was conducted on 90 adult dry human mandibles from the South Indian population, irrespective of age and sex. The location, shape, orientation and the presence of the accessory foramen were studied by visual examination. The size and position of the mental foramen were measured by using a digital vernier caliper. The SPSS, version 15 software was used for the statistical analysis, to calculate the minimum, maximum, incidence, mean and standard deviation. Results: In a majority of the mandibles, the mental foramen was located at the level of the root of the 2nd premolar, midway between the inferior margin and the alveolar margin of the mandible. Most of the mental foramina were oval in shape. The orientation of the foramen was postero-superior in 83% of the mandibles. The accessory foramens were noted in five mandibles. Conclusion: The knowledge on the variations in the position and size of the mental foramen and the presence of the accessory foramen may be of much use to dental surgeons.